Penerapan LKS berbantuan Virtual Laboratory dalam Pembelajaran Inquiry Terbimbing terhadap Pencapaian Kompetensi Siswa - Putri Auliyani; Ramli Ramli; Zulhendri Kamus (PILLAR OF PHYSICS EDUCATION, 2018)
Physical learning is related to practicum activities. Practicum is conducted by students using virtual laboratory. practicum activities that using virtual laboratory, requires student worksheet (LKS) and guided inquiry model. The purpose of the using LKS assisted virtual laboratory in learning guided inquiry is to see the effect on the student competences of class X SMA Negeri 5 Padang. The type of the research is quasi experiment with posstest only. Population of the research is the students of class X SMA Negeri 5 Padang academic year 2017/2018. Sampling technique using purposive sampling technique. The research was conducted on student competences, namely attitude, knowledge, and skill competencies. Instrument of research used observation sheet for attitude competency, postest for knowledge competence, and performance rating sheet for competency skill. The research data were analyzed by t test. The t test is performed for the competence of knowledge and skill, while for the attitude competence is analyzed using graph. The result of data analysis for the student competences after using LKS assisted by virtual laboratory in learning guided inquiry, the result obtained as follows: 1) the average value of physics learning result in attitude competence has continuous improvement, 2) the average value of physics learning result at both sample classes are 83.82 and 79.52 for knowledge competence; 3) average physics learning outcomes in both sample classes are 85.71 and 82.06 for skill competencies.